Permeating partially hydrated GCLs with jet fuel at temperatures from −20°C and 20°C. Issue 6 (1st November 2005) - Hurst, P.; Rowe, R. K.; Mukunoki, T.
Abstract : The hydraulic conductivity of hydrated and partially hydrated geosynthetic clay liners (GCLs) with respect to Jet Fuel A-1 (Arctic diesel) is examined at −20°C, −5°C, 5°C, and 20°C. Methods developed to hydrate GCLs to specific water contents (60%, 90%, 120%) and subject them to subzero temperatures without the additional uptake of water are described. Results indicate that there are two main mechanisms that affect the hydraulic conductivity of Jet Fuel A-1. For a constant bulk void ratio, as the water content increases, the hydraulic conductivity with respect to Jet Fuel A-1 decreases. Similarly, for a constant water content, as bulk void ratio decreases, the hydraulic conductivity with respect to Jet Fuel A-1 decreases. GCLs at positive temperatures with an initial degree of saturation ( S r ) greater then 0.77 had a hydraulic conductivity with respect to Jet Fuel A-1 of less than 10 −9 m/s, whereas GCLs at subzero temperatures with S r > 0.70 had a hydraulic conductivity with respect to Jet Fuel A-1 of less than 2.5 × 10 −10 m/s. Highly saturated ( S r > 0.85) GCLs at subzero temperatures were essentially impermeable, having a hydraulic conductivity with respect to Jet Fuel A-1 of less than 10 −12 m/s. The hydraulic conductivity of hydrated and partially hydrated geosynthetic clay liners (GCLs) with respect to Jet Fuel A-1 (Arctic diesel) is examined at −20°C, −5°C, 5°C, and 20°C. Methods developed to hydrate GCLs to specific water contents (60%, 90%, 120%) and subject them to subzero temperatures without the additional uptake of water are described. Results indicate that there are two main mechanisms that affect the hydraulic conductivity of Jet Fuel A-1. For a constant bulk void ratio, as the water content increases, the hydraulic conductivity with respect to Jet Fuel A-1 decreases. Similarly, for a constant water content, as bulk void ratio decreases, the hydraulic conductivity with respect to Jet Fuel A-1 decreases. GCLs at positive temperatures with an initial degree of saturation ( S r ) greater then 0.77 had a hydraulic conductivity with respect to Jet Fuel A-1 of less than 10 −9 m/s, whereas GCLs at subzero temperatures with S r > 0.70 had a hydraulic conductivity with respect to Jet Fuel A-1 of less than 2.5 × 10 −10 m/s. Highly saturated ( S r > 0.85) GCLs at subzero temperatures were essentially impermeable, having a hydraulic conductivity with respect to Jet Fuel A-1 of less than 10 −12 m/s.